BREAK-EVEN POINT ANALYSIS AS A DECISION-MAKING INSTRUMENT IN SHARIA BUSINESS - Kartini, Kartini (Universitas Muhammadiyah Surabaya, 2025)
Break-Even Point (BEP) is a financial analysis tool used to determine the breakeven point in a business, where total revenue equals total costs, resulting in neither profit nor loss. In the context of Islamic business, the application of BEP has distinct characteristics compared to conventional business due to the adherence to Islamic principles, such as the prohibition of riba (usury), gharar (uncertainty), and maisir (gambling). This study aims to analyze the fundamental concept of BEP in Islamic business, its role in decision-making, its differences from conventional business, and the challenges in its implementation. The research method employed is a qualitative approach with descriptive analysis based on literature studies and a review of Islamic business practices. The findings indicate that BEP in Islamic business serves as a strategic tool for setting selling prices, cost efficiency, and profit management by Islamic values. The primary differences from conventional business are in the financing methods, which utilize Shariah-compliant contracts, and the social obligations such as zakat, which also influence BEP calculations. However, challenges in applying BEP in Islamic business include a lack of understanding among business owners, limited Shariah accounting standards, and variability in the profit-sharing system. Therefore, education, clearer Islamic accounting standards, and support from Islamic financial institutions are necessary to ensure a more effective implementation of BEP in Shariah-compliant businesses.